Desymmetrized Leaning Pillar[6]arene - Wu, Jia‐Rui; Mu, Anthony U.; Li, Bao; Wang, Chun‐Yu; Fang, Lei; Yang, Ying‐Wei (Angewandte Chemie International Edition, 2018)
In this work, a novel version of macrocyclic arenes, namely leaning pillar[6]arenes, was discovered and it can be considered as a tilted version of a pillar[6]arene with two hydroxy/alkoxy functionalities removed. Through a facile two‐step synthetic approaches, in conjunction with a diversity of post‐modification possibilities, a series of leaning pillar[6]arenes, with good cavity adaptability and enhanced guest‐binding capability, was synthesized, and their self‐assembly in single‐crystal states is presented. DFT calculations demonstrated that the lower rotational barrier of unsubstituted phenylene rings, the uneven electron density centered at the leaning phenyl rings, and the polarization effect along the edge generated by the hydrogen‐bond‐induced orientation of hydroxy groups greatly affected the host‐guest properties, and meanwhile provided an intuitive explanation for the pillar‐like and rigid structure of traditional pillar[6]arenes. Significantly, the crystal structure of cyclo‐oligomeric quinone was obtained by direct oxidation of leaning pillar[6]arenes. A lean‐to: A series of backbone‐desymmetrized pillararenes, namely leaning pillar[6]arenes, has been designed and successfully synthesized. They exhibit interesting three‐dimensional packing structures and enhanced host‐guest properties.